1987
DOI: 10.1200/jco.1987.5.9.1469
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with oral drug therapy in patients with hematologic malignancy.

Abstract: Compliance with oral self-administered allopurinol (daily medication) and prednisone (intermittent medication) as well as compliance with monthly scheduled clinic appointments, were examined in 108 patients with newly diagnosed hematologic malignancy. Baseline levels of compliance (control group) were compared to results obtained after implementation of three intervention packages, whose aim was to increase compliance. The packages included combinations of education, home psychologic support and restructuring,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(76 citation statements)
references
References 17 publications
2
74
0
Order By: Relevance
“…25 However, patients may overestimate their adherence to oral cancer therapies by a factor of two in discussions with their physicians. 26 A recent study showed that adherence to imatinib therapy among some patients with Ph þ CML is less than ideal (Tsang et al, J Clin Oncol 2006; 24: 330s. abstract 6119).…”
Section: Factors Affecting Imatinib Plasma Pk Exposurementioning
confidence: 99%
“…25 However, patients may overestimate their adherence to oral cancer therapies by a factor of two in discussions with their physicians. 26 A recent study showed that adherence to imatinib therapy among some patients with Ph þ CML is less than ideal (Tsang et al, J Clin Oncol 2006; 24: 330s. abstract 6119).…”
Section: Factors Affecting Imatinib Plasma Pk Exposurementioning
confidence: 99%
“…The medical record is also a source of prescriptions ordered, modifications to the regimen, and adherence. [19][20][21][22][23][24][25][26][27] However, medical records are known to be incomplete or inaccurate. 28 When electronic medical records are fully implemented, this may become a more reliable source of information.…”
Section: Indirect Methods Of Measuring Adherencementioning
confidence: 99%
“…MEMS is not considered to be a practical tool in the clinical setting due to its excessive cost. Pill counts 7,56 and medical record clinical note audits occurred, [19][20][21][22][23]25,62 yet were not very common, probably due to the labor intensive nature of conducting these measures. Direct serum or urine 55,57 measures were rare in adults, yet very common in pediatric oncology.…”
Section: An Integrative Review Of Literature On Measurement Of Adherementioning
confidence: 99%
“…11 When biologic measures, such as urine or serum assays are used, specific ranges of blood or urine levels are expected to be associated with adherence to a medication regimen. 12,13 The operational definition of adherence is dependent upon which of these measures, or combination of these measures, is used to assess adherence.…”
Section: Operational Definition Of the Health Status Outcome Adherencementioning
confidence: 99%